The Effect of Financial Information on Stock Underpricing With Underwriter Reputation as A Moderating Variable - Maya Laura Listi; I Nyoman Wijana Asmara Putra (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Underpricing continues to be a prominent issue within the Indonesian capital market, as many firms conducting an Initial Public Offering (IPO) tend to set initial share prices below their subsequent market value. This research investigates the moderating role of underwriter reputation in the relationship between profitability, financial leverage, and earnings per share (EPS) on IPO underpricing among firms listed on the Indonesia Stock Exchange (IDX). Utilizing a purposive sampling technique, the study analyzes data from 176 companies. The data are processed using Moderated Regression Analysis (MRA) with the help of STATA software. The findings reveal that profitability, measured by return on assets (ROA), significantly influences underpricing. In contrast, financial leverage (proxied by the debt-to-equity ratio) and EPS show no statistically significant effect. Moreover, underwriter reputation is shown to moderate the negative impact of both ROA and EPS on underpricing but does not moderate the relationship between the debt-to-equity ratio and underpricing. These results offer valuable insights into signaling theory and information asymmetry, highlighting the importance of firm fundamentals and intermediary reputation in IPO pricing strategies. The study contributes to a better understanding for investors, issuers, and regulators involved in the IPO decision-making process.